Compliance with Planning Standards Related to the Setbacks around Domestic Buildings: Empirical Evidence from Kenya - Wilfred Ochieng Omollo (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
This study investigates the extent to which planning standards that regulate the setbacks around domestic buildings are complied with by developers in Kenya, a case study of Kisii Town. Using proportional random sampling targeting seven neighbourhoods, a sample of 364 was drawn from the target population of 7430 developments. While checklists were used to collect data on the extent of compliance with the planning standards, data were analyzed using means, mode, standard deviation and a one-sample t-test. Results established that most developments disregarded the planning standards on setbacks. Hypothesis tests further reported significant differences between the respective recommended setbacks (front, side and rear) and extent of developers’ compliance, t (289) = -14.746, p = .000; t (289) = -8.937, p = .000; and t (289) = -20.3826, p = .000. The study concludes that developers flout planning standards owing to insufficient development control by the County Government of Kisii. A recommendation is made for the adoption of locally nurtured standards that addresses the existing socioeconomic attributes as an alternative of relying on those generated at the national level. This study enriches the current body of literature in planning by validating how compliance with planning standards may be statistically assessed.